Dry‐Season Greening and Water Stress in Amazonia: The Role of Modeling Leaf Phenology. Issue 6 (16th June 2018) - Manoli, Gabriele; Ivanov, Valeriy Y.; Fatichi, Simone
Abstract: Large uncertainties on the sensitivity of Amazon forests to drought exist. Even though water stress should suppress photosynthesis and enhance tree mortality, a green‐up has been often observed during the dry season. This interplay between climatic forcing and forest phenology is poorly understood and inadequately represented in most of existing dynamic global vegetation models calling for an improved description of the Amazon seasonal dynamics. Recent findings on tropical leaf phenology are incorporated in the state‐of‐the‐art eco‐hydrological model Thetys & Chloris. The new model accounts for a mechanistic light‐controlled leaf development, synchronized dry‐season litterfall, and an age‐dependent leaf photosynthetic capacity. Simulation results from 32 sites in the Amazon basin over a 15‐year period successfully mimic the seasonality of gross primary productivity; evapotranspiration (ET); as well as leaf area index, leaf age, and leaf productivity. Representation of tropical leaf phenology reproduces the observed dry‐season greening, reduces simulated gross primary productivity, and does not alter ET, when compared with simulations without phenology. Tolerance to dry periods, with the exception of major drought events, is simulated by the model. Deep roots rather than leaf area index regulation mechanisms control the response to short‐term droughts, but legacy effects can exacerbate multiyear water stress. Our results provide a novel mechanistic approach to model leaf phenology and flux seasonality in the tropics, reconciling the generally observed dry‐season greening, ET seasonality, and decreased carbon uptake during severe droughts. Key Points: A mechanistic description of tropical leaf phenology for ecosystem models is presented Model simulations for 32 sites in the Amazon realistically reproduce carbon/water fluxes Leaf phenology explains dry‐season greening with little impact on evapotranspiration fluxes